(untitled) (Third Sector Social Economic Review, 2019)
In this study; it is aimed to investigate production and foreign trade of marble sector in natural stone industry in Turkish economy and in this context, it is aimed to determine the competitiveness of marble products. Competitive power calculations were made by us with using Revealed Comparative Advantage (RCA) method. Base on results, it is determined that Turkey generally has high competitiveness on marble industry products but as an exception it is evaluated that has no competition power on granite.